Chromosome-Level Genome Assembly of Bupleurum chinense DC Provides Insights Into the Saikosaponin Biosynthesis - Zhang, Quanfang; Li, Min; Chen, Xueyan; Liu, Guoxia; Zhang, Zhe; Tan, Qingqing; Hu, Yue; Fan, Yangyang; Liu, Yanyan; Zhu, Tongshan; Yang, Xue; Yue, Mingming; et al. (Frontiers in Genetics, 2022)
Bupleurum chinense DC. is a widely used traditional Chinese medicinal plant. Saikosaponins are the major bioactive constituents of B. chinense DC. Saikosaponins biosynthesis in Bupleurum has been more intensively studied than any other metabolic processes or bioactive constituents. However, whole-genome sequencing and chromosome-level assembly for Bupleurum genus have not been reported until now. In order to know the genetic basis of the biosynthesis of saikosaponins, we first report a high-quality chromosome-level genome of B. chinense DC. The genome was phased into haplotype 0 (621.27 Mb with a contig N50 of 16.86 Mb and a scaffold N50 of 92.25 Mb) and haplotype 1 (600.48 Mb with a contig N50 of 23.90 Mb and a scaffold N50 of 102.68 Mb). A total of 45,909 and 35,805 protein-coding genes were predicted in haplotypes 0 and 1, respectively. The enrichment analyses suggested that the gene families that expanded during the evolution of B. chinense DC are involved in the biosynthesis of isoquinoline alkaloid, tyrosine, and anthocyanin. Furthermore, we analyzed the genes involved in saikosaponin biosynthesis and determined the candidate P450 and UGT genes in the third stage of saikosaponins biosynthetic, which provided new insight into the saikosaponins biosynthetic. The genomic data provide a valuable resource for future investigations of the molecular mechanisms, biological functions, and evolutionary adaptations of B. chinense DC.